Three-dimension correction of Charcot ankle deformity with a titanium implant. Issue 1 (1st January 2021) - Wang, Gang; Lin, Junhao; Zhang, Hong; Pei, Yantao; Zhu, Lei; Xu, Qingjia
Abstract: Background: Charcot neuroarthropathy of the ankle is an extremely challenging clinical dilemma, and its surgical management can be highly complicated. The goal of Charcot ankle treatment is to to restore a plantigrade and stable foot, and thus to avoid ulceration with subsequent infection. This report aims to introduce a method of correcting ankle deformity using a novel 3D printing technique. Patient and methods: One patient with Charcot ankle deformity was operated in this study. The ankle deformity of this patient was quantified in three dimensions through computed tomography. On the basis of the computed tomography scans, a new titanium implant was designed and manufactured using 3D printing. The implant was applied in the surgery of tibio-talo-calcaneal arthrodesis to restore local anatomy of the affected ankle of the patient with Charcot neuroarthropathy. Results: Evaluation of the post-operative radiography indicated union in the affected ankle. After surgery, the planar foot in this patient was restored. The patient was satisfied with the post-operative course, and joint fusion was successful as indicated by 2-year post-operative evaluation. The results of post-operative follow-up showed that the lower limb length of the patient with Charcot neuroarthropathy was salvaged, and the patient retained the plantigrade foot. Conclusion: Three-dimensional printing technique combined with tibio-talo-calcaneal arthrodesis may help to correct ankle deformity in patients with Charcot neuroarthropathy.